Spatial Heterogeneity of Soil Chemical Properties in a Subtropical Karst Forest, Southwest China - Zhonghua Zhang; Baoqing Hu; Gang Hu (The Scientific World Journal)
This study evaluates the spatial heterogeneity of the soil chemical properties of surface soils across a 1 ha old-growth subtropical karst forest in southwest China.